1976
DOI: 10.1002/art.1780190210
|View full text |Cite
|
Sign up to set email alerts
|

The arthropathy of relapsing polychondritis

Abstract: Twenty-three adults (11 males and 12 females) with well-defined relapsing polychondritis (RP) are studied in order to characterize the arthropathy of RP. Arthritis was found in 19 patients-as the presenting feature in 8 and as a significant symptom in 11 others. The usual pattern of involvement was migratory, asymmetric, nonnodular, nonerosive, and seronegative, and affected large and small joints as well as parasternal articulations. In addition RP was seen in 3 patients with preexisting chronic polyarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 10 publications
0
11
0
5
Order By: Relevance
“…Joint involvement is usually migratory, affecting large and small joints and often parasternal articulations. Generally, is is nonerosive and seronegative [25]. Nasal inflammation, laryngotracheal cartilage inflammation and ocular inflammation are less common at initial presentation and occur in approximately 20% of patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Joint involvement is usually migratory, affecting large and small joints and often parasternal articulations. Generally, is is nonerosive and seronegative [25]. Nasal inflammation, laryngotracheal cartilage inflammation and ocular inflammation are less common at initial presentation and occur in approximately 20% of patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of polyarthritis in more than 80% of the patients with RP [8] might possibly also be explained by type-specific autoimmunity. A recent experiment has shown that intradermal injection of collagen type 11 whether isolated from articular cartilage or vitreous collagen induced a chronic polyarthritis in rats whereas collagen types I and III or proteo glycans were not arthritogenic [11].…”
Section: Discussionmentioning
confidence: 99%
“…Articular manifestations (arthralgia, arthritis, and costochondritis) may occur in 70%-80% of adult and pediatric patients 1-3. The most common pattern is episodic, asymmetric, nonerosive, nondeforming peripheral arthritis, lasting for weeks or months, commonly affecting ankles, wrists, PIP joints, metacarpophalangeal joints, elbows, and metatarsophalangeal joints [3][4][5] . Plain radiographs, in the absence of an associated disease, classically show only juxtaarticular osteopenia and minor uniform joint space narrowing, typically without erosive changes or deformities 6,7 .…”
Section: To the Editormentioning
confidence: 99%